Rivaroxaban and Hemostasis in Emergency Care - Jürgen Koscielny; Edita Rutkauskaite (Emergency Medicine International)
Rivaroxaban is an oral, direct Factor Xa inhibitor, approved for the prevention and treatment of several thromboembolic disorders. Rivaroxaban does not require routine coagulation monitoring and has a short half-life. However, confirmation of rivaroxaban levels may be required in circumstances such as life-threatening bleeding or perioperative management. Here, we explore the management strategies in patients receiving rivaroxaban who have a bleeding emergency or require emergency surgery. Rivaroxaban plasma concentrations can be assessed quantitatively using anti-Factor Xa chromogenic assays, or qualitatively using prothrombin time assays (using rivaroxaban-sensitive reagents). In patients receiving long-term rivaroxaban therapy who require elective surgery, discontinuation of rivaroxaban 20–30 hours beforehand is normally sufficient to minimize bleeding risk. For emergency surgery, we advise against prophylactic use of hemostatic blood products, even with high rivaroxaban concentrations. Temporary rivaroxaban discontinuation is recommended if minor bleeding occurs; for severe bleeding, rivaroxaban withdrawal may be necessary, along with compression or appropriate surgical treatment. Supportive measures such as blood product administration might be beneficial. Life-threatening bleeding demands comprehensive hemostasis management, including potential use of agents such as prothrombin complex concentrate. Patients taking rivaroxaban who require emergency care for bleeding or surgery can be managed using established protocols and individualized assessment.